Juventudes, escolarização e projetos futuros: narrativas de jovens alunos/as do Ensino médio de uma escola pública de Maceió - Rodrigues, Mariana Costa (2018)
The aim of the research was to understand the narratives of the young people who attend the third year of high school about their experiences of schooling. The research presents a qualitative approach, being characterized by a case study, and uses as methodological instruments the observation, the application of questionnaires and narrative interviews (BERTAUX, 2010) with young people of a state public school located in Maceió. Youth is understood as a social category characterized by the plurality of experiences, ideas and characteristics. We discuss the conceptions of life projects based on the studies of some authors such as Schutz (1979) and Dayrell (2005), verifying the relation between them and the process of schooling for the young. As a theoretical contribution, we present the contributions of authors such as Schutz (1979), Kuenzer (2000), Bauman (2001), Velho (2003), Spósito (2004), Dayrell (2007) and Carrano (2011). The results show that young people intend to continue their studies by entering higher and / or technical courses, thus increasing the level of schooling. Getting a job and paying for a private college appears as one of the key strategies thought by young people. The main motivations for thinking about these projects are related to the support and encouragement of the family or the identification of young people in activities already developed, such as apprenticeship as a young apprentice. Young people recognize the importance of basic schooling to achieve their goals, yet they describe the structural, material and relationship difficulties with teachers and school management as limitations to a better course during high school. Considers, therefore, from the data and testimony of young people that although the school is considered essential to reflect on their future projects, it still needs to go further in order to broaden the discussions with these young people about these projects within the school.